Comparative Analysis of Healthy Lifestyles in Peruvian University Students During and After the COVID-19 Pandemic - Carme Y. Baltazar-Meza; María Custodio (The Scientific World Journal)
The COVID-19 pandemic has provoked a worldwide mental health crisis, affecting university students in an exacerbated way, exposing them to the risk of emotional isolation and development of eating disorders. The present study aimed to examine the quality of healthy lifestyle practices in university students from the Faculty of Human Medicine and the Faculty of Education of a Peruvian university during and after the COVID-19 pandemic. This study was conducted during the academic period 2020 and 2023. Data collection was performed between July and August 2020, during the first wave of the COVID-19 pandemic (M1) and between November and December 2023, post-pandemic (M2). In M1 and M2, 370 and 82 students participated, respectively. The results of the Mann–Whitney test revealed significant differences between the total healthy lifestyle score of students in M1 and M2. In the nutrition domain, there are significant differences between the scores obtained in M1 and M2, revealing a decrease in nutritional care. Significant differences were also found between both faculties in substance use in M1 and physical activity practice in M2. Although a trend toward the adoption of healthy habits was observed in the initial stages, the longitudinal analysis reveals a generalized decrease in concern for health and well-being. Medical students, on the other hand, showed greater resilience and more successful adaptation to new circumstances, evidencing the importance of academic training in the promotion of healthy lifestyles. These results underscore the need to implement intervention strategies aimed at promoting healthy habits in the student population, especially in contexts of health crisis.